2007
DOI: 10.1002/pbc.20943
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low‐energy laser in the prevention of oral mucositis in children with cancer receiving chemotherapy

Abstract: This study showed no evidence of benefit from the prophylactic use of low-energy laser in children and adolescents with cancer treated with chemotherapy when optimal dental and oral care was provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
15

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 18 publications
2
74
0
15
Order By: Relevance
“…The Cochrane prevention metaanalysis [41] analyzed two studies [16,18] that together showed an 80 % reduction in the incidence of severe mucositis in HSCT. It concluded that overall there is weak evidence from two small studies at some risk of bias that lowenergy laser application may be beneficial in preventing severe mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane prevention metaanalysis [41] analyzed two studies [16,18] that together showed an 80 % reduction in the incidence of severe mucositis in HSCT. It concluded that overall there is weak evidence from two small studies at some risk of bias that lowenergy laser application may be beneficial in preventing severe mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Por ser uma técnica não invasiva, simples e atraumática, sem relatórios clínicos de toxicidade, a aplicação de luz é ideal para o tratamento de tecidos sem risco de danificar as células saudáveis [30][31][32][33][34][35][36][37][38][39][40][41][42][43] .…”
Section: Revisão Da Literatura Terapia a Laserunclassified
“…Alguns autores estudaram a interferência de infecções virais e fúngicas relativamente à expressão de mucosite, entretanto não avaliamos estes aspectos neste trabalho, apenas controlando expressões de candidose pesudomembranosa aguda, que não constituíram ocorrência importante (DJURIC et al, 2007;NICOLATOU-GALITIS et al, 2006;PIZZO, 1993SARAL et al, 1981SCHUBERT et al, 1990;SONIS, 2002). Na clínica onde foi desenvolvido o projeto, A literatura abriga diversos trabalhos que ensaiaram a aplicação do laser de baixa potência com a intenção de prevenir a instalação da mucosite oral conseqüente à quimioterapia (ANTUNES et al, 2007;BARASCH et al, 1995COWEN et al, 1997CRUZ et al, 2007;MIGLIORATI et al, 2001;SCHUBERT et al, 2007). Entretanto, a maioria deles foi realizada em pacientes submetidos ao transplante de medula óssea, onde o indivíduo recebe condicionamento quimioterápico único, que por sua vez é bastante diverso daquele utilizado pelos pacientes portadores de carcinoma de cólon.…”
Section: Discussionunclassified
“…Assim sendo, seria mais eficiente e proveitoso, economicamente, manter protocolo de aplicações preventivas especialmente para esses pacientes, apenas controlando aqueles que não desenvolverem mucosite mais severa nesses primeiros ciclos, disponibilizando a estes a intervenção terapêutica do laser. É também estabelecido que os cuidados gerais de manutenção da saúde bucal, proporcionados por um estomatologista, são determinantes para um maior conforto e redução dos graus de severidade da mucosite oral associada à quimioterapia (CRUZ et al, 2007).…”
Section: Discussionunclassified